Enhancing Student Achievement in Circle Theorems: Integrating Computer Animation with the Jigsaw Cooperative Learning Model - Opoku Nyantah, Rahmat; Kena Frempong , Nana; Larbi , Ernest (EDUPEDIA Publisher, 2025)
Purpose – Geometry plays a crucial role in developing cognitive skills such as spatial reasoning, visualization, and problem-solving. However, many students in Ghanaian senior high schools face difficulties with abstract topics like circle theorems. This study examines the effectiveness of combining jigsaw cooperative learning with computer animation to improve students’ conceptual understanding of geometric concepts compared to traditional teaching methods. Methodology – A quasi-experimental design was adopted involving senior high school students assigned to control and experimental groups. The control group received conventional instruction, while the experimental group was taught using jigsaw cooperative learning supported by computer animations. Pre-test and post-test data were collected and analyzed using the Mann-Whitney U test due to non-normal data distribution. Findings– Students in the experimental group significantly outperformed those in the control group, demonstrating higher post-test scores. The integration of cooperative learning and visual animation enhanced conceptual understanding, reduced cognitive load, and improved knowledge retention. Novelty – This study offers a unique contribution by integrating jigsaw learning with computer animation—a combination rarely explored in teaching abstract geometry. Conducted in a sub-Saharan African context, it extends limited research on multimedia-supported instruction by focusing not only on academic performance but also on deeper cognitive outcomes. Significance – The findings underscore the potential of technology-enhanced collaborative strategies in improving learning in abstract mathematical domains. The study provides evidence-based recommendations for adopting innovative pedagogies in low-resource educational settings, with implications for curriculum development and teacher training.